A year of operation of Melibea e-Callisto Solar Radio Telescope. (July 2015) - Russu, A; Gómez-Herrero, R; Prieto, M; Monstein, C; Ivanov, H; Rodríguez-Pacheco, J; Blanco, J J
Abstract: The e-CALLISTO (Compound Astronomical Low-cost Low-frequency Instrument for Spectroscopy and Transportable Observatory) is a worldwide radio-spectrograph network with 24 hours a day solar radio burst monitoring. The e-CALLISTO network is led by the Swiss Federal Institute of Technology Zurich (ETHZ Zurich), which work up collaborations with local host institutions. In 2013 the University of Alcalá joined the e-CALLISTO network with the installation of two Solar Radio Telescopes (SRT): the EA4RKU-SRT that was located at the University of Alcalá from January 2013 till June 2013 and the Melibea-SRT that is located at Peralejos de las Truchas (Guadalajara) in operation from June 2013. The Spanish e-Callisto SRTs provide routine data to the network. We present examples of type III and type II radio-bursts observed by Melibea during its first year of operation and study their relation with soft X-ray flares observed by GOES and Coronal Mass Ejections (CMEs) and Solar Energetic Particle (SEP) events observed by space-borne instrumentation.